Penentuan biaya produksi dengan metode direct costing sebagai dasar penetapan harga jual pada UD Lourdes Tompasobaru - Kolompoy, Claudio; Pusung , Rudy J.; Maradesa , Djeini (Manajemen Bisnis dan Keuangan Korporat, 2024)
Direct costing is an accounting method used to calculate production costs. This method only calculates production costs that are directly related to the product and can be traced directly to the product. Normal pricing is the determination of the selling price which is determined by adding future costs with a percentage mark up or addition above the total costs calculated using a certain formula. The aim of this research is to determine the determination of production costs using the direct costing method as the basis for determining selling prices. The type of research used is descriptive qualitative. The results of this research show that there is a difference between determining production costs using the company's simple calculation method and calculations using the direct costing method. Because of this difference in the selling price determination between the owner (actual) and according to direct costing with normal pricing, there is a quite high difference, where the selling price determined by the company is higher than according to the direct costing method with normal pricing.